البلاغة منهجا وتعليما وتعلما من وجهة نظر طلاب كلية اللغات والإدارة = The rhetoric: curriculum, teaching and learning from the perspective of the students of the Faculty of Languages and Management. - Hassan, Fekri Abidin; Eltingari, Salih Mahgoub Mohamed; Youssef, Mohamed Abdelrahman Ibrahim (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh, 2019)
يَدْرُسُ هذا البحث مادّة البلاغة منهجاً، وتعليماً، وتعلّماً في كليّة اللُّغات والإدارة التابعة للجامعة الإسلاميّة العالميّة في ماليزيا، من خلال المنهج الوصفيّ التحليليّ الميدانيّ، وقد تمَّ تصميم استبيان، ومن ثمَّ وُزِّع على أفراد العينة البالغ عددها 33 مفحوصًا. وبعد التحليل تمَّ التوصل إلى نتائج منها: يجد أفراد العينة صعوبة في الانتقال من الحقيقة إلى المجاز مباشرة، وذلك لخلو المنهج من مادة عن الآداب العربيّة، أفراد العينة غير مدركين لوجود أبواب بلاغيّة يدرسونها، ولا وجود لها في القرآن الكريم، والحديث النبوي، ضرورة الاعتماد على القرآن الكريم والحديث النبوي عند استخلاص الأمثلة البلاغية، والبعد قدر الإمكان عن الشعر، أفراد العينة لا يحبون المشاركة داخل الفصل. وقد أوصى البحث بضرورة الربط بين الكنايات والمجازات الموجودة في لُغة الدارس الأم، والعربيّة. *************************************************************************************** This research studies the subject of rhetoric, from curriculum, teaching and learning aspects, at the Faculty of Languages and Management of the International Islamic University Malaysia, through the analytical descriptive method, a questionnaire was designed and then distributed to a sample of 33 students. After analysis, the following results were obtained: The sample finds it difficult to move directly from reality to metaphor, this is because the curriculum does not contain Arabic literature, members of the sample are not aware of the existence of rhetorical chapters for them to study, and it is not existent in the Holy Quran, and the prophetic traditions, the need to rely on the Holy Quran and Hadith when drawing rhetorical examples, and to stay as much as possible from poetry, members of the sample does not like to participate in the classroom. The research has recommended the need to link the metonymy and allegory in the student’s mother tongue with Arabic language.